Transformasi Kurikulum Dayah Terpadu Aceh: Integrasi-Interkoneksi Keilmuan - Astuti, Dewi; Zulkhairi, Zulkhairi (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2025)
This study aims to analyse the development and transformation of the curriculum in integrated Islamic boarding schools (dayah terpadu) in Aceh, with a particular focus on the integration–interconnection of classical Islamic scholarship (turāṡ) and modern sciences. The study is grounded in the urgency of curriculum modernization in Aceh, which is shaped by regulatory dynamics, globalization, and the significant growth of Islamic boarding schools over the past two decades. A qualitative library research approach was employed, drawing on primary sources (classical texts, official regulations, and historical archives) and secondary sources (academic articles, books, and research reports). Data were analysed using thematic-historical and hermeneutic approaches. The findings reveal that the transformation of the curriculum in Aceh’s integrated dayah unfolds across four stages: policy, implementation, evaluation, and follow-up. This process signifies an epistemological evolution rather than a mere pragmatic adaptation, emphasizing the integration of Islamic sciences (‘ulūmuddīn) with modern knowledge, informed by Tyler’s curriculum theory, Kuntowijoyo’s and Azra’s integration paradigm, Al-Faruqi’s Islamization of knowledge, and Al-Attas’s concept of ta’dīb. The study concludes that the transformation of the integrated dayah curriculum in Aceh represents a civilizational project that safeguards Islamic traditions while responding to the challenges of global modernity.